What Belongs in Copyright? - Liu, Joesph P. (The Columbia Journal of Law & the Arts, 2016)
The title of my talk today is, “What Belongs in Copyright?” When Jane invited me to speak, she asked me to provide a “more Olympian perspective” on the issues of authorship, originality, and fixation that are the subjects of today’s conference. And while I don’t pretend to have any Zeus-like powers of insight or observation, I do hope to provide at least some general thoughts about the question implied by the title of this conference, namely, what properly belongs within the scope of copyright. In particular, I want to spend some time talking about how copyright law constructs the box that defines what is inside copyright and outside. I will start by very briefly surveying some of the doctrines that define what can be copyrighted. I will then talk a bit about what theory or set of theories we might look at to help decide these difficult boundary cases, to help decide what belongs in that box. And finally, at the very end I will suggest that underlying all of these doctrines and theories are relatively unexamined aesthetic judgments about what counts as copyrightable subject matter, judgments that we should probably take more expressly into account when deciding when something is copyrightable. My goal in these remarks is not so much to provide any specific answers, but to set the table and provide some general frameworks for the more detailed discussion to come.